The positive role of the tourism industry for Dubai City in the United Arab Emirates - Harith Yas; Abbas Mardani; Yas Kh. Albayati; Shamma Essa Lootah; Dalia Štreimikienė (Contemporary Economics, 2020)
Several types of research have been conducted regarding the tourism industry in Dubai. However, they have not managed to indicate the roles that the tourism industry plays in Dubai. The purpose of the current study is to examine the roles of tourism in Dubai and the growth of tourism, as well as to uncover relevant information that supports the development of the tourism industry in Dubai. The current paper discusses the infrastructure, strategies, and culture, which enhance the growth of the tourism industry in Dubai. The development of the Burj Khalifa, the tallest building in Dubai and in the world, is indicative of the touristic aspirations of the city. The study also factors in the top tourist destinations, the top ten countries visiting Dubai, as well as the busiest airports in the world (data from travel com- panies). In the literature review, the authors discuss some of the developments brought by the tourism industry in Dubai, including cultural and infrastructure development, such as roads and airports. The paper indicates the natural features available in Dubai that makes the Dubai tourism industry flourish. The findings indicate that cultural and religious diversity , hospitality and infrastructure enhance the growth of Dubai's tourism industry. Other notable mentions, such as the Expo 2020 Dubai and the Sheik Muhammed Vision 2020 awards are also discussed. The current study highlights the developments the tourism industry has brought to Dubai and the strategies to improve the sector. The paper can also be implemented to further the research on the tourism industry in other countries.
Keywords: L83; N15; O44; 330; Dubai; tourism; urban development; culture; management; urban planning